2022
DOI: 10.1039/d1ra06267k
|View full text |Cite
|
Sign up to set email alerts
|

Simulations reveal that antimicrobial BP100 induces local membrane thinning, slows lipid dynamics and favors water penetration

Abstract: MD simulations reveal that BP100 peptide induces local membrane thinning and negative curvature, slows lipid dynamics and increases the water life time in the lipid hydrophobic core and transmembrane water transport in the direction of the peptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 97 publications
1
11
0
Order By: Relevance
“…1 B–D) were selected from the Antimicrobial Peptide Database 48 (APD3, https://aps.unmc.edu ) based on their similarity with a previously studied SCHAMP, BP100 (Fig. 1 A) 37 , 38 . They are short peptides (11–13 aminoacids), amphiphilic in alpha-helix conformation, which is their predominant secondary structure when in contact with negatively charged membranes 21 , 36 , 40 , 41 , 43 , 44 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 B–D) were selected from the Antimicrobial Peptide Database 48 (APD3, https://aps.unmc.edu ) based on their similarity with a previously studied SCHAMP, BP100 (Fig. 1 A) 37 , 38 . They are short peptides (11–13 aminoacids), amphiphilic in alpha-helix conformation, which is their predominant secondary structure when in contact with negatively charged membranes 21 , 36 , 40 , 41 , 43 , 44 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous data suggest negatively charged membranes favor the occurrence of peptide flip 37 , in which the amphiphilic peptide approaches the membrane with its polar side and then it turns, facing the membrane with its non-polar side and burying the peptide into the membrane core. In order to compare with previous results obtained with BP100 37 , 38 , we simulated peptides on a mixed bilayer of palmitoyloleoylphosphatidylcholine (POPC) and palmitoyloleoylphosphatidylglycerol (POPG) in a 1:1 mol/mol ratio. Membranes containing 64 lipids on each leaflet were assembled using PACKMOL 56 and were solvated with the TIP3P water model, with an average of 55 water molecules per lipid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides lipid bilayer thinning and thickening, also the curvature of the membrane is an important aspect regarding its morphology. In biological processes like endocytosis and vesiculation, a change of the membrane's curvature has been observed and plays a crucial role in them 149 . Researchers synthesized the amphipathic helical peptide EpN18 (XSTSSLRRQXKNIVHNYS–amide, X = norleucine) that derived from the N‐terminus of the protein epsin‐1.…”
Section: Membrane Composition/morphology Changes Induced By Peptide I...mentioning
confidence: 99%
“…142 them. 149 Researchers synthesized the amphipathic helical peptide EpN18 (XSTSSLRRQXKNIVHNYS-amide, X = norleucine) that derived from the N-terminus of the protein epsin-1. They found that the incorporation of EpN18 in HeLa cells led to packing defects in the membrane (Figure 12).…”
Section: Membrane Composition/ Morphology Changes Induced By Peptide ...mentioning
confidence: 99%